2018
DOI: 10.1186/s12877-018-0959-0
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength in old and oldest old Swiss adults – a cross-sectional study

Abstract: BackgroundHandgrip strength is indicative of overall physical health and mobility in the elderly. A reduction in strength below a certain threshold severely increases the risk of mobility limitations and is predictive for adverse outcomes such as dependence in daily activities and mortality. An overview of age- and geography- specific handgrip strength values in older adults provide a reference for further investigations and measures in clinical practice to identify people at risk for clinically meaningful wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 41 publications
(53 reference statements)
2
22
3
1
Order By: Relevance
“…Two studies of younger populations from Korea and Japan reported lower prevalences of people with low handgrip strength (14.6% in men and women combined [22], 17.2% in men and 10.1% in women [23]). The differences between the previous studies and the present results may be explained by the age differences (mean age 76 years in their studies versus 83 years in the present study) and/or ethnic origin of the study population [22,23], since handgrip strength declines with age [39] and is reportedly lower in Asian than in European countries [42].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Two studies of younger populations from Korea and Japan reported lower prevalences of people with low handgrip strength (14.6% in men and women combined [22], 17.2% in men and 10.1% in women [23]). The differences between the previous studies and the present results may be explained by the age differences (mean age 76 years in their studies versus 83 years in the present study) and/or ethnic origin of the study population [22,23], since handgrip strength declines with age [39] and is reportedly lower in Asian than in European countries [42].…”
Section: Discussioncontrasting
confidence: 96%
“…Generalizability of the results to the French-, Italian-and Romansh-speaking parts of Switzerland as well as to other countries is dependent on region-specific variation in handgrip strength. However, given that handgrip strength of adults 75 years and over in German-speaking Switzerland is similar to that of northern European countries, such as Denmark [39], the results of the current study are likely to be representative for older people from other northern and central European countries. Secondly, the subgroup of male participants was relatively small compared to the total population studied but is useful since published data from men > 80 years are rare.…”
Section: Limitationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Functional status was better among individuals aged 65 and over [66]. Hand grip strength decreased with age [67,68], explaining a lower score in our result, in favor of higher prevalence of sarcopenia (See Additional file 3).…”
Section: Comparison With Younger Elderly Comparison With Individual Amentioning
confidence: 59%
“…This instrument contains a list of the most common problems in older people and this study considered cardiovascular problems, hypertension, diabetes, hearing loss, and dementia; Handgrip strength was assessed using a dynamometer considering four attempts, two on each hand. The final score corresponds to the average of the highest values for each hand (Wearing et al, 2018;Zammit et al, 2019).…”
Section: Instrumentsmentioning
confidence: 99%